THE CONCEPT OF ISLAMIZATION OF SCIENCE: A STUDY OF THE EDUCATIONAL PHILOSOPHY OF SYED MUHAMMAD NAQUIB AL-ATTAS - Hasim, Muhamad Fuad; Al Mubarak, Ahmad Jundi; Taufiq, Mirwan Akhmad; Ramadhani, Arya Pratama; Al-Hakim, Ahmad Ghulam Zaidirrohman; Masitho, Dewi Nur; Hariadi, Dedi; Rachmawati, Emilia; Wahid, Abdurrahman; Arif, Mohammad Nuzulul Qodri; Utama, Adi Surya; Azhari, Saefullah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract: This study critically examines Syed Muhammad Naquib al-Attas’s concept of Islamization of knowledge, highlighting its original contribution to the reform of contemporary Islamic education. Unlike prior descriptive studies, this research identifies a conceptual gap in the discourse and offers a critical synthesis of al-Attas’s thought. It employs library research using a conceptual-hermeneutic analytical approach to his primary texts. The findings show that al-Attas’s Islamization is not merely a critique of the West, but an integrative project placing revelation as the epistemic foundation, adab as the basis of education, and tawhid as its ontological framework. The study also reveals that his concept can be practically applied to address current challenges such as secularism, identity crisis, and the science-religion dichotomy in Islamic education. By contextualizing al-Attas’s principles in light of today’s educational issues, this study offers both theoretical and practical contributions for revitalizing Islamic curricula grounded in tawhid and epistemic integrity. Keywords : Knowledge, Naquib al-Attas, Islamization